2021
DOI: 10.32672/jse.v6i3.3117
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Waktu Milling Terhadap Sifat Desorpsi Material Penyimpan Hidrogen MgH2-Ni Melalui Teknik Mechanical Alloying

Abstract: Hydrogen is a renewable energy source that can be used as a fuel and as an  alternative to fossil fuels. Solid  storage media in solid form are safer to use than liquid (-253 oC) or gaseous media (700 bar) media. To store hydrogen in a solid medium, it requires a metal able to  interact with hydrogen . Magnesium is one of the metals which  can form metal hybrids based on MgH2 which is capable of  absorbing hydrogen up to  (7.6wt%). However, the reaction kinetics for  magnesium are  very slow, it takes at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…NaOH is used in this study because silica can The peak width value of the silica samples decreased significantly so that the phase of each sample analyzed could be identified. The smaller the peak width, the closer the crystal phase of the silica sample will be [24]. The results of the analysis showed that the un-calcined silica sample…”
Section: Silica Extractionmentioning
confidence: 99%
“…NaOH is used in this study because silica can The peak width value of the silica samples decreased significantly so that the phase of each sample analyzed could be identified. The smaller the peak width, the closer the crystal phase of the silica sample will be [24]. The results of the analysis showed that the un-calcined silica sample…”
Section: Silica Extractionmentioning
confidence: 99%